A Power in Transition? An Analysis of the EU´s Role Conception through the Global Gateway Initiative - Stecker,Klara (2023)
Born into the context of tense geopolitical competition, the Global Gateway Initiative has shown the motivation of the European Union to take on a more ambitious role as a global actor. A trend in the academic literature hints at a shift towards a more pragmatic and geopolitically oriented paradigm in the EU´s foreign policy. In order to investigate how the EU envisions its own role, this paper adopts a theoretical framework based on role conception. Qualitative content analysis is used to analyse communication material published by the European Union on the Global Gateway Initiative. The results suggest that the EU´s role conception is ambiguous. In conclusion, this paper provides three hypotheses arguing that the inconclusive results hint at the EU being a “power in transition”, a “power in crisis” or a political actor with a complicated decision–making process.
Keywords: European Union; Role Conception; Global Gateway Initiative; Geopolitics; Belt and Road Initiative